Potencialidade da recuperação de pastagem de Brachiaria decumbens fertilizada com camas de aviário e fontes minerais - Silva, Adriane de Andrade (2005)
CHAPTER II: The poultry keeping is one of the main farming activities of the region of the Triângulo Mineiro, enters the organic residues produced the chicken manure presents potentiality to be used in the recovery of areas degraded under pasture vegetation. So that developed the experiment in a typical dystrophic red Latossol under pasture of Brachiaria decumbens in advanced state of degradation for evaluate the influence of the application the mineral fertilizer and chicken manure in chemical alterations of the soil, the absorption of nutrients and foodstuffs characteristics of the Brachiaria decumbens. The delineation was mounted in DBC, where had been used five treatments (control, one mineral dosage, three exclusive dosages of chicken manure (1,200; 2,400 and 4,800 kg ha-1) and one mix the 2,400 chicken manure + mineral fertilizer dosage). The application of the residue was the throwing and had been carried through 2 collections the soil (March and August of 2004) and four plant collections (two in the period of rain season and two in the period of dry season). The fertilization with chicken manure increased the productivity of the MS of the forage; it increased the crude protein (CP), it kept texts of NDF; ADF and Lignin of the forage. It promoted increments in the absorption of nutrients N; P; K and supplied micronutrients the forage. As organic seasoning, the chicken manure presented high agronomic efficiency with residual effect until the 120 days for N; P; K; did not modify in the applied dosages the chemical characteristics of the soil how much to texts OM; pH; P and K. CHAPTER III: The breeding of turkey desenvolving in Brazil principal and Last decade, in the virtue of increase the demand of market external and inside. Although this similar characteristics presentable into residues of chicken manure and turkey manure, she necessary evaluate thes particulates that residue in recovery the grazing degraded. So that developed the experiment in a typical dystrophic red Latossol under pasture of Brachiaria decumbens in advanced state of degradation for evaluate the influence of the application the mineral fertilizer and turkey manure in chemical alterations of the soil, the absorption of nutrients and foodstuffs characteristics of the Brachiaria decumbens. The delineation was mounted in DBC, where had been used five treatments (control, one mineral dosage, three exclusive dosages of turkey manure (1,200; 2,400 and 4,800 kg ha-1) and one mix the 2,400 turkey manure + mineral fertilizer dosage). The application of the residue was the throwing and had been carried through 2 collections the soil (March and August of 2004) and four plant collections (two in the period of rain season and two in the period of dry season). The fertilization with turkey manure increased the productivity of the MS of the forage; it increased the crude protein (CP), it support e/or reduce of NDF; ADF and Lignin of the forage. It promoted increments in the absorption of nutrients N; P; K and supplied micronutrients the forage. As organic seasoning, the turkey manure presented high agronomic efficiency with residual effect until the 120 days for N; P; K. Not modify in the applied dosages the chemical characteristics of the soil how much to texts OM; pH; P and K.